2004
DOI: 10.1139/y04-058
|View full text |Cite
|
Sign up to set email alerts
|

What visual information is used for navigation around obstacles in a cluttered environment?

Abstract: The goal of this study was to determine what visual information is used to navigate around barriers in a cluttered terrain. Twelve traffic pylons were arranged randomly in a 4.55 x 3.15 m travel area: there were 20 different arrangements. For each arrangement, individuals (N = 6) were positioned in 1 of 3 locations on the outside border with their eyes closed: on verbal command they were instructed to open their eyes and quickly go to 1 of 2 specified goals (2 vertical posts defining a door) located on one edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…If the summed area was zero, our model would perfectly replicate the baseline trajectory. This error measurement is based on a similar measure used by Patla, Tomescu, and Ishac (2004). In addition, we also compute the maximum linear distance between the trajectory steered by our model and the baseline, which gives a worst-case measure of how far our model deviates from the correct path.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the summed area was zero, our model would perfectly replicate the baseline trajectory. This error measurement is based on a similar measure used by Patla, Tomescu, and Ishac (2004). In addition, we also compute the maximum linear distance between the trajectory steered by our model and the baseline, which gives a worst-case measure of how far our model deviates from the correct path.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…A recent study by Patla, Tomescu, and Ishac (2004) calls into question the idea that steering control is purely reactive, even in a static environment. They had subjects walk through an arrangement of 12 randomly placed traffic cones covering a 4.55 m × 3.15 m area toward a goal object.…”
Section: Discussionmentioning
confidence: 99%
“…Heading is adapted according to the distance and the angle between the walker and stationary goals and obstacles: goals act as attractors and obstacles as repellors. Other authors suggested that path planning precedes dynamic control to navigate in a cluttered environment [14]. From a local point of view, some studies focused on the circumvention of non-human static obstacles [19].…”
Section: Collision Avoidance In the Real Worldmentioning
confidence: 99%
“…The various complexities of these environmental contexts require different navigational skills implicating both the motor and cognitive aspects of the control of locomotion. Normal human behavior during obstacle circumvention is beginning to be understood in children [1], young adults [2][3][4][5], and older adults [6,7]. Understanding how trained athletes view environmental space and navigate will provide additional insights into adaptive locomotor control.…”
Section: Introductionmentioning
confidence: 99%
“…Patla et al [3] argued that considering only the next obstacle in the travel path is not the strategy used to navigate a cluttered environment. They provided some evidence that path planning is not based on detailed geometrical information about the environment, but rather on avoiding obstacle clusters in the line-of-sight travel path.…”
Section: Introductionmentioning
confidence: 99%